Mexiletine in spinal and bulbar muscular atrophy: a randomized controlled trial. Issue 11 (8th October 2022) - Yamada, Shinichiro; Hashizume, Atsushi; Hijikata, Yasuhiro; Inagaki, Tomonori; Ito, Daisuke; Kishimoto, Yoshiyuki; Kinoshita, Fumie; Hirakawa, Akihiro; Shimizu, Shinobu; Nakamura, Tomohiko; Katsuno, Masahisa
Abstract: Objective: Patients with spinal and bulbar muscular atrophy (SBMA) often experience muscular weakness under cold exposure. Methods: In our previously conducted observational study, we assessed nerve conduction and grip strength to examine the effect of cold exposure on motor function, based on which we conducted a randomized controlled trial to evaluate the efficacy and safety of mexiletine hydrochloride in SBMA (MEXPRESS). Results: In the observational study, 51 consecutive patients with SBMA and 18 healthy controls (HCs) were enrolled. Of the patients with SBMA, 88.0% experienced cold paresis. Patients with SBMA exhibited greater prolongation of ulnar nerve distal latency under cold (SBMA, 5.6 ± 1.1 msec; HC, 4.3 ± 0.6 msec; p  <0.001); the change in the distal latencies between room temperature and cold exposure conditions correlated with the change in grip power. In the MEXPRESS trial, 20 participants took mexiletine or lactose, three times a day for 4 weeks with a crossover design. There was no difference in distal latencies at room temperature and under cold exposure between mexiletine and placebo groups as the primary endpoint. However, tongue pressure and 10‐sec grip and release test under cold exposure were improved in the mexiletine group. There were no serious adverse events throughout the study period. Interpretation: Cold paresis is common and associated with prolongation of distal latency in SBMA. The results of the phase II clinical trial revealed that mexiletine showed short‐term safety, but it did not restore cold exposure‐induced prolongation of distal latency.